MyData ecosystem from a value perspective : A case study on smart mobility - Wäck, Ada-Maria (My University, 2020)
In today’s digital world, companies are increasingly connected, forming ecosystems that enable global partner networks to integrate their offerings and resources to co-create unique value. Similarly, digitization has allowed people to become more connected than ever, and the online actions and interactions result in an incomprehensibly vast digital footprint. One valuable resource formed in ecosystems is the personal data of users that is collected and utilized by organizations for multiple purposes often without transparency to the individual. As a response, MyData, a novel human-centric approach to data management, has emerged aiming towards decentralized value constellations that provide transparency to individuals, business opportunities to organizations and develop both human rights and information technology for a more sustainable society. This study investigates MyData ecosystems from a value perspective by studying the ecosystem’s value proposition to an individual and how value is created and captured in the context of MyData. The research was conducted as a qualitative case study. Thematic interviews were used as an empirical method to explore the novel topic by enabling unpredictable insights and topics to be identified. Five interviewees were interviewed during March – April 2020. Thematic networks were used as a tool for organizing and analysing data. The findings of this study suggest that the value proposition of the MyData ecosystem to an individual is two-fold. First, economic and functional value is derived from data-driven, customer centric services and second, data control and transparency are achieved through human-centric data management. Furthermore, the framework based on existing theory and empirical findings provides the blueprint of ecosystem value creation and capturing with new insight into the roles of different actors. The framework suggests that in ecosystems, individuals can adopt roles that allow generating economic value. Moreover, a fifth actor, the ecosystem regulator is identified. Finally, the study helps to explain how actors capture value directly and indirectly. Besides theoretical contribution, the research findings benefit organizations by providing insight in the potential roles these organizations can capture value with in a MyData ecosystem. Moreover, the value creation principles provide understanding of the requirements and benefits organizations must apply and can expect when engaging in the ecosystem.

Yritykset ovat nykyisessä, digitaalisessa maailmassa entistä verkostoituneempia muodostaen ekosysteemejä, joissa globaalien kumppaniverkostojen on mahdollista integroida tarjoomansa sekä resurssinsa luodakseen yhdessä ainutlaatuista arvoa. Digitalisaation seurauksena myös ihmiset ovat verkostoituneempia kuin koskaan aiemmin ja laajentavat digitaalista jalanjälkeään verkossa tapahtuvien toimintojen ja interaktioiden myötä. Yksilön digitaalinen jalanjälki muodostuu datasta, jota yritykset hyödyntävät ilman, että yksilöillä itsellään on aina läpinäkyvyyttä siihen, mihin dataa käytetään. Tämän johdosta kehitetty MyData on uusi, ihmiskeskeinen lähestymistapa datan hallintaan. Sen tavoitteena on luoda hajautettuja arvomuodostelmia, jotka mahdollistavat paremman hallinnan ja läpinäkyvyyden yksilölle, liiketoimintamahdollisuuksia yrityksille ja jotka johtavat kestävämpään yhteiskuntaan kehittäen ihmisoikeuksia ja informaatioteknologiaa rinnakkain. Tässä tutkimuksessa tutkitaan MyData-ekosysteemiä arvonäkökulmasta, keskittymällä ekosysteemin arvolupaukseen yksilölle, arvon luontiin sekä siihen, kuinka ekosysteemitoimijat voivat saada osan luomastaan arvosta. Tutkimus on toteutettu laadullisena tapaustutkimuksena teemahaastattelujen avulla, mahdollistaen uusien aiheiden esiintymisen datankeruun aikana. Viisi haastattelua ajoittuivat maalis-huhtikuulle 2020. Tutkimuksessa hyödynnettiin temaattisia verkostoja datan jäsentämiseen ja analysointiin. Tutkimuksen löydösten mukaan ekosysteemin arvolupaus yksilölle muodostuu datan hallinnasta ja läpinäkyvyydestä sekä taloudellisesta ja funktionaalisesta arvosta datalähtöisten, asiakaskeskeisten palveluiden myötä. Teorian ja empirian pohjalta luotu viitekehys kuvaa arvolupauksen lisäksi arvon luomista, arvon saantia sekä ekosysteemitoimijoiden rooleja. Tutkimustulokset tarjoavat entistä kattavamman näkemyksen yksilön rooleista ekosysteemissä, joiden myötä myös yksilö voi saada taloudellista arvoa osana ekosysteemiä. Lisäksi tulokset ehdottavat viidettä toimijaa, ekosysteemin sääntelijää, sekä auttavat ymmärtämään kuinka toimijat voivat saada arvoa osana ekosysteemiä. Tulokset tuovat yrityksille ymmärrystä mahdollisista rooleista MyData-ekosysteemissä, minkä pohjalta yritykset voivat rakentaa liiketoimintaa. Lisäksi tutkimuksessa kuvatut ekosysteemiperiaatteet arvonluonnin takana luovat ymmärrystä MyDatan asettamista vaatimuksista ja mahdollistamista hyödyistä.
Keywords: MyData, ecosystem-as-structure, value creation, value capturing